The Comparison of Heart Rate Variability and Energy Expenditure of Chess Players between Chess Game and Physical Activity - Coskun Rodoplu; Ramiz Arabaci; Recep Gorgulu (Lithuanian Sports University, 2022)
Background. A game of chess represents a legitimate physical and psychological stress due to its strategic and cognitively demanding nature over a long period of time. This very challenging situation has not been thoroughly explored and, to the best of our knowledge, there is no research report that has concentrated on both heart rate variability and energy expenditure for deeper understanding of chess players' performance. The main aim of the present study was to examine the HRV and EE of chess players before, during and after a competition, as well as the moderate level of running exercise. Methods. The sample comprised 24 (19 men, 5 women; Mage=24.8) volunteer chess players who have been playing chess regularly for at least 5 years. The average National Chess Rating (NCR) of participants was determined as 1526. In addition, a total of ten participants have International Chess Rating (ELO) rating (mean = 1588). We obtained participants' body mass indexes before the experiment took place. Participants' HR and HRV were taken through the chess competition, and running exercises took place in 3 different time periods; before (15 min), during (30 min) and after (15 min). Results. Our results indicated that there was a significant difference on HRV between chess competition and running exercises HRV (RMSSD, SDNN, NN50 and RR) (p=.001). Besides, there was a significant difference on participants' EE between a chess competition and a moderate level of running (p=.001). Conclusions. HRV values determined in chess competition and running exercise are different from each other. Contradictory to our speculative hypothesis, the current results provide that a moderate level of running exercises requires more energy expenditure than a chess game. Keywords: running exercise, mental activity, autonomic nervous system, parasympathetic activity.